Parametric study of rider’s comfort in a vehicle with semi-active suspension system under transient road conditions - Arinola Bola Ajayi; Ediketin Ojogho; Surajudeen Adedotun Adewusi; Sunday Joshua Ojolo; Julio Cesar Costa Campos; Antonio Marcos de Oliveira Siqueira (The Journal of Engineering and Exact Sciences)
Considering that many Nigerian roads are untarred, the effect of frequent plying of these untarred roads on passengers and the expected performance of suspension system of vehicles are important for health and safety reasons. This is significant because the transmission of vibration associated with suspension systems are dependent on the frequency spectrum of the road input, and the nature of the suspension system and the vehicle seating arrangement that is producing the vibration. Thus, this study focuses on the discomfort experienced by passengers based on parametric study of vehicle with semi-active suspension system under transient road conditions.  The modeling of the of semi-active vehicle suspension system properties are contrived on the mass- spring damper system for 4 degree-of–freedom half- car model integrated with 3 degrees of freedom human-seat arrangement. Using vehicle parameters, the severity of ride discomfort experienced by the passenger as the vehicle traversed transient road conditions (i.e., traversing obstruction) was evaluated in terms of the vibration dose value (VDV). Results of simulation based on the parametric studies are presented and the vibration dose values evaluated to show the dependence of vehicle ride comfort on the characteristics of the various elements of the vehicle suspension such as stiffness and damping characteristics. The result showed that the variation of sprung mass and suspension stiffness of the vehicle had more significant effects on passenger discomfort than the variation of the unsprung mass. The parametric study also revealed that suspension stiffness affects the suspension working space as the vehicle traversed transient road condition.